Investigation of the Visible Light-Sensitive ZnO Photocatalytic Thin Films - Nadareishvili, M. M.; Mamniashvili, G.; Jishiashvili, D.; Abramishvili, G.; Ramana, C.; Ramsden, J. (Engineering, Technology & Applied Science Research, 2020)
ZnO photocatalytic thin films deposited on a glass substrate are obtained by chemical spraying technique, and they are active in the visible light spectrum. Optical studies have shown that ZnO thin films doped by nickel impurities absorb visible light at wavelengths from 400nm to 600nm. At the same time, this absorption rate increases with the increase of concentration of nickel impurities. At high concentration (5%), the absorption of light is reduced in the visible area, but after heat treatment at 6000C the light absorption in these samples improves, which allows us to conclude that the observed effect is caused by a violation of the homogeneity of the distribution of nickel impurities and the creation of agglomerates. Decoration of ZnO thin film surfaces by silver clusters improves light absorption, as it happens to the nanopowders, but in the case of thin films, this effect is much smaller. Experiments on methylene blue determine the significance of photocatalytic activity in the visible area of sun irradiation of ZnO thin films containing nickel impurities, which are obtained by chemical spraying technique.